Optimizing Risk Management and Operational Efficiency in Self-Propelled Oil Barge Operations Using AHP and FMEA: A Case Study at PT. Faher Hayat Bersatu - Bondatama, Nofrizal; Hendayani, Ratih (eProceedings of Management, 2025)
This study aims to optimize risk management and operational efficiency in self-propelled oil barge operations at PT.Faher Hayat Bersatu. As part of the maritime logistics sector, the company operates in an environment that demandsboth high reliability and strong risk mitigation strategies. Effective decision-making under such conditions requires astructured, data-driven approach that can address both performance priorities and operational vulnerabilities. To achievethis, the study integrates two well-established methodologies: the Analytic Hierarchy Process (AHP) and Failure Modeand Effects Analysis (FMEA). The AHP method is used to determine the relative importance of various operationalcriteria and sub-criteria, with results indicating that “Fuel Cost” and “Timely Delivery” are the most critical factors.Concurrently, FMEA is utilized to assess potential failure modes, identifying “Fuel Leakage” as having the highest RiskPriority Number (RPN), marking it as the most severe risk. The integration of AHP and FMEA provides acomprehensive framework that enables companies to prioritize operational focus areas while systematically addressingthe risks associated with them, thereby supporting strategic planning and continuous performance improvement.Keywords: AHP, FMEA, Risk Management, Operational Efficiency, Oil Barge